2021
DOI: 10.17762/turcomat.v12i3.2038
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Covid-19 pandemic and firm’s performance towards unemployment across countries

Abstract: As a result of the consequences of the Covid-19 pandemic, stock market players issued their quick response on how coronavirus has affected the performance of firms whereby most of the affected sectors are airlines, tourism, hotels, transportation and many more. This has led to an increase in the unemployment rate worldwide.  Considering this global issue, this study was aimed at investigating the relationship between unemployment with a number of confirmed cases of Covid-19 and firms’ performance as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Hal ini dimungkinkan jika kinerja perusahaan E-Commerce meningkat. Penelitian yang dilakukan oleh Saad (2021) menyatakan bahwa peningkatan jumlah kasus terdampak Covid-19 akan memengaruhi kinerja usaha yang dikendalikan oleh faktor ekonomi makro yang mengarah pada hubungan positif yang signifikan antara tingkat pengangguran di semua negara dalam penelitiannya. Oleh karena itu, perlu dilakukan peningkatan kinerja usaha, khususnya usaha E-Commerce karena memiliki peluang yang lebih besar di era digital saat ini.…”
Section: Jawaunclassified
“…Hal ini dimungkinkan jika kinerja perusahaan E-Commerce meningkat. Penelitian yang dilakukan oleh Saad (2021) menyatakan bahwa peningkatan jumlah kasus terdampak Covid-19 akan memengaruhi kinerja usaha yang dikendalikan oleh faktor ekonomi makro yang mengarah pada hubungan positif yang signifikan antara tingkat pengangguran di semua negara dalam penelitiannya. Oleh karena itu, perlu dilakukan peningkatan kinerja usaha, khususnya usaha E-Commerce karena memiliki peluang yang lebih besar di era digital saat ini.…”
Section: Jawaunclassified
“…Firm efficiency and profitability can be strengthened only with a hygienic environment and social distancing policies to reduce the impact of the Covid-19 pandemic (Imran et al, 2021). Other research in Malaysia concluded that the increase in Covid-19 cases and the Movement Control Order (MCO) policy would directly impact decreasing business performance and increasing unemployment (Saad, 2021). Similar research in Malaysia concluded that the consumer goods industry experienced an increase in liquidity ratios, profitability, and activity while the property, real estate and construction, finance, trade, services, and investment industry decreased their liquidity and profitability (Khatib & Nour, 2021).…”
Section: Introductionmentioning
confidence: 98%